Lessons for Development from London Business School's Centre for New and Emerging Markets (CNEM) Research Project 'Investment in Emerging Markets' - Estrin, Saul (Washington, DC: World Bank, 2012)
The nature of a country's institutional and policy environment, especially the quality of the legal framework and the predictability of government policy, is critical for attracting foreign direct investment (FDI). FDI is also affected by the quality of locally available resources, notably human capital, supplier industries and infrastructure. Policymakers should not look to FDI primarily as a source of employment creation: the main benefits instead derive from spillovers that improve competitiveness. Policies aimed at enhancing competitiveness of local firms also make an industry more attractive for foreign investors.